Hydrogen sulfide alleviates pericarp browning in lichi fruit by modulating energy and sugar metabolisms - Gao, Zhaoyin; Zhao, Kunkun; Zhang, Zhengke; Nizamani, Mir Muhammad; Li, Songgang; Li, Min; Gong, Deqiang; Wang, Jiabao; Hu, Meijiao (Frontiers in Plant Science, 2024)
Postharvest litchi is susceptible to browning that limits the development of litchi industry. Hydrogen sulfide (H2S) is an important bioactive molecule that can regulate many physiological processes. This study examined the effects of exogenous H2S on pericarp browning and related physiological mechanisms in postharvest litchi. The results exhibited that exogenous H2S treatment delayed the browning of litchi pericarp and reduced the damage to cell membrane integrity during storage. This treatment inhibited the energy losses of litchi fruit by increasing the activities of H+-ATPase, Ca2+- ATPase, cytochrome C oxidase (CCO) and succinate dehydrogenase (SDH) and regulating the expression of energy metabolism-related genes, including LcAtpB, LcSnRK2, LcAAC1, LcAOX1 and LcUCP1. In addition, H2S treatment increased the levels of fructose, glucose, sucrose, inositol, galactose and sorbose in litchi fruit, and promoted sucrose synthesis by regulating the activities of sucrose phosphate synthase (SPS), sucrose synthase (SS), acid invertase (AI) and neutral invertase (NI). Based on the current findings, we suggest that exogenous H2S enhances the energy supply and antioxidant activity of litchi by modulating energy and sugar metabolism, thereby inhibiting fruit browning and senescence. These results indicated that H2S treatment is an effective approach to maintaining the quality of litchi fruit and extending its shelf life.